2021
DOI: 10.1038/s41374-020-00505-1
|View full text |Cite
|
Sign up to set email alerts
|

Loss of sphingosine 1-phosphate receptor 3 gene function impairs injury-induced stromal angiogenesis in mouse cornea

Abstract: Sphingosine 1-phosphate (S1P) is a bioactive sphingolipid generated through sphingosine kinase1 (SPK1)-mediated phosphorylation of sphingosine. We show here that injury-induced S1P upregulation increases corneal neovascularization through stimulating S1PR3, a cognate receptor. since this response was suppressed in S1PR3-knockout mice. Furthermore, Cayman10444, a selective S1PR3 inhibitor, reduced this response in WT mice. Such reductions in neovascularization were associated with reduced vascular endothelial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Abnormal proliferation and migration of ASMCs play an important role in airway hyperresponsiveness and airway remodeling in asthma [ 108 , 116 , 117 ]. S1P is a natural, multifunctional, bioactive phospholipid molecule that is involved in cell proliferation, differentiation, migration, contraction, and vasculogenesis [ 82 , 108 , 118 120 ]. It is reported that the level of S1P in bronchoalveolar lavage fluid is significantly increased in asthmatic patients, and the S1P stimulates the proliferation, migration, and contraction of ASMC in vitro [ 108 ].…”
Section: The Hippo Signaling Pathway and Respiratory Diseasesmentioning
confidence: 99%
“…Abnormal proliferation and migration of ASMCs play an important role in airway hyperresponsiveness and airway remodeling in asthma [ 108 , 116 , 117 ]. S1P is a natural, multifunctional, bioactive phospholipid molecule that is involved in cell proliferation, differentiation, migration, contraction, and vasculogenesis [ 82 , 108 , 118 120 ]. It is reported that the level of S1P in bronchoalveolar lavage fluid is significantly increased in asthmatic patients, and the S1P stimulates the proliferation, migration, and contraction of ASMC in vitro [ 108 ].…”
Section: The Hippo Signaling Pathway and Respiratory Diseasesmentioning
confidence: 99%
“…In addition, we used rhodamine phalloidin to stain the cytoskeleton, and found that the inhibition of S1PR3 significantly reduced the LPS-induced disruption of the cytoskeleton. Moreover, Yasuda et al [ 41 ] reported that the S1PR3 mediated the VE-cadherin mRNA levels in two types of endothelial cells. In a murine ventilator-induced lung injury model, S1PR3 induced endothelial barrier loss through ADAM10-mediated VE-cadherin cleavage [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although investigations on S1P in the cornea have been under documented in the past, two recent studies have demonstrated the effects of SphK1/S1P in mouse corneas. Yasuda et al, 2021, revealed that TGF-β1-induced injury increased S1P via SphK1 upregulation modulated by S1PR3 and VEGF-A and angiogenesis [104]. Wilkerson et al, 2022, reported that SphK1 knockout mice had reduced corneal neovascularization following injury [55].…”
Section: Discussionmentioning
confidence: 99%